The effect of temperature on giant magnetostrictive thin films in high pre-stress environment for sensor application - Singh P.K.; Pareta A.S.; Bhushan A.; Panda S.K.; Shyam Kumar M.B. (My University, 2025)
The high pre-stress environment arises in the manufacturing of amorphous thin films of Terfenol-D through sputtering techniques. The pre-stress thin film of Terfenol-D has been developed due to the mismatch in the thermal coefficient of deposited magnetostrictive film and substrate. In the presence of high pre-stress anisotropic energy has been changed and due to that magnetization and magnetostriction properties of the thin film are affected. A novel three-dimensional hyperbolically generalized constitutive model for giant magnetostrictive materials along with vector generalized Jiles-Atherton hysteresis model was considered for predicting the hysteretic responses precisely under thermo-elasto-magnetic field. The material constants for the generalized constitutive models are taken from calibrated physical and experimental evidence. A non-linear finite element model for the thin films made up of Terfenol-D has been developed for investigating the thermo-elasto-magnetic characteristics, using COMSOL Multiphysics software. The predicted thermo-elasto-magnetic results have been critically analyzed the effect of temperature, the orientation of the applied magnetic field, and in-plane stresses condition. Hence, the present study can be decisive for the development of a more reliable and robust design of magnetostrictive film-based intelligent devices. © 2023 Elsevier Ltd. All rights reserved.